The Jurisprudential Regulations of Preventive Medicine and Their Impact on Preserving Life and Society: An Analytical and Applied Study - سعدالدين أحمد وليد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This research explores the jurisprudential rulings grounded in the objectives of preventive medicine, drawing upon the foundational Islamic legal maxim: "No harm shall be inflicted or reciprocated." The study begins by defining preventive medicine linguistically and terminologically, followed by an examination of its significance in protecting individuals and communities from health-related risks. It adopts a methodology that integrates Islamic legal principles with contemporary medical perspectives. The research outlines a number of Islamic legal rulings aimed at preventing illness, mitigating its progression, curbing its spread, or avoiding delays in recovery. These include prohibitions such as lingering in unsanitary places due to potential health harm, the use of sun-heated water due to the risk of diseases like vitiligo, and permissions such as performing dry ablution (tayammum) when water use could worsen a condition or delay healing. It also discusses exemptions from attending Friday and congregational prayers for those who fear harm to themselves or others due to illness or contagion, the permissibility of breaking fast for patients at risk of health deterioration, and for those experiencing severe sexual desire that may cause physical harm, such as genital fissures. Furthermore, the study addresses rulings related to fear of disease transmission, including the loss of custody rights by a mother with a contagious disease such as leprosy or vitiligo, in order to protect the child, and the permissibility of annulling a marriage contract if one spouse is diagnosed with a contagious disease that negatively affects marital life. In relation to contemporary reality, the study applies these rulings to the case of viral hemorrhagic fevers as a model illustrating the relevance of activating Islamic legal principles in confronting modern epidemics. Emphasis is placed on adhering to quarantine protocols, isolation, avoiding gatherings and handshakes, and implementing all necessary measures to reduce infection transmission, in alignment with the objectives of Islamic law in preserving life.